2014
DOI: 10.1007/s12264-013-1468-6
|View full text |Cite
|
Sign up to set email alerts
|

Regional homogeneity abnormalities in patients with tensiontype headache: a resting-state fMRI study

Abstract: Tension-type headache (TTH) is the most prevalent type of primary headache. Many studies have shown that the pathogenesis of primary headache is associated with fine structural or functional changes. However, these studies were mainly based on migraine. The present study aimed to investigate whether TTH patients show functional disturbances compared with healthy subjects. We used restingstate functional magnetic resonance imaging (fMRI) and regional homogeneity (ReHo) analysis to identify changes in the local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 26 publications
3
48
1
Order By: Relevance
“…A decreased functional or structural changes in the DLPFC of patients with chronic pain was also reported in previous studies 30, 34–36 . Our results corroborated these previous studies.…”
Section: Discussionsupporting
confidence: 85%
“…A decreased functional or structural changes in the DLPFC of patients with chronic pain was also reported in previous studies 30, 34–36 . Our results corroborated these previous studies.…”
Section: Discussionsupporting
confidence: 85%
“…The same group also reported connectivity abnormalities within the DMN as well as the Table 2 Comparison of different resting state functional connectivity studies in migraine with aura Mainero et al 12 Hadjikhani et al 13 Present study central executive network, the salience network [31] and in networks involving the basal ganglia [32]. Intrinsic connectivity has also recently been reported in other headache disorders: reduced regional homogeneity analysis values in several brain areas in tension-type headache [35], increased connectivity between the hypothalamus and several areas during attack periods in cluster headache patients [36], and both increased and decreased connectivity involving the precuneus in medication-overuse headache [37]. Intrinsic connectivity has also recently been reported in other headache disorders: reduced regional homogeneity analysis values in several brain areas in tension-type headache [35], increased connectivity between the hypothalamus and several areas during attack periods in cluster headache patients [36], and both increased and decreased connectivity involving the precuneus in medication-overuse headache [37].…”
Section: Discussionmentioning
confidence: 56%
“…The authors further reported several other abnormalities in interictal MO patients using other analysis strategies: regional homogeneity analysis [33] and amplitude of low-frequency fluctuation [34]. Intrinsic connectivity has also recently been reported in other headache disorders: reduced regional homogeneity analysis values in several brain areas in tension-type headache [35], increased connectivity between the hypothalamus and several areas during attack periods in cluster headache patients [36], and both increased and decreased connectivity involving the precuneus in medication-overuse headache [37]. It is currently not known if intrinsic connectivity abnormalities are present in the ictal or pre-ictal phase of migraine.…”
Section: Discussionmentioning
confidence: 73%
“…Studies of people with COPCs indicate that in response to painful stimuli, similar brain regions, including those that integrate and process sensory information, cognition and affect, show increased activity or are "activated." [332][333][334][335][336][337][338][339][340][341][342][343][344][345][346][347] A more recent advance in the use of fMRI is to look at patterns of connectivity among different brain regions, either while a person is at rest or performing a specific task. 348 A resting state analysis enables one to evaluate brain changes associated with chronic spontaneous pain, as well as examine how chronic pain may disrupt non pain-related functions, such as cognition.…”
Section: Abnormal Pain and Sensory Processingmentioning
confidence: 99%